Printing preparation method of TBC battery and TBC battery

By using the printing preparation method during the preparation process of TBC batteries, the corrosion contact silver paste was first printed and the low-solid conductive welding silver paste was then printed, which solved the problem of high silver paste consumption in TBC batteries, and achieved the effect of reducing costs and improving cost-effectiveness.

CN119584672APending Publication Date: 2025-03-07DAS SOLAR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411661718.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The consumption of silver paste by TBC batteries during the preparation process is high, resulting in an increase in costs. The prior art is difficult to effectively reduce the consumption of silver paste.

Method used

A printing preparation method is adopted to prepare corrosion contact silver paste and low-solid conductive welding silver paste, respectively, and the surface of the semi-finished TBC battery is printed and sintered to form a gate line and a conductive welding layer.

Benefits of technology

Through this method, the overall silver paste consumption of TBC batteries is reduced, the production cost is reduced, and the overall cost-effectiveness of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119584672A_ABST
    Figure CN119584672A_ABST
Patent Text Reader

Abstract

The invention discloses a printing preparation method of a TBC battery and the TBC battery, and the printing preparation method comprises the following steps: firstly preparing corrosion contact type silver paste, preparing low-solid-content conductive welding type silver paste, then printing the corrosion contact type silver paste on a first surface of a TBC battery semi-finished product to form a grid line, and drying the TBC battery semi-finished product printed with the corrosion contact type silver paste; wherein the first surface of the TBC battery semi-finished product comprises first areas and second areas which are alternately arranged in an interdigital mode, the grid lines are formed in the first areas and the second areas respectively, finally, low-solid-content conductive welding type silver paste is overprinted on the grid lines, the TBC battery semi-finished product overprinted with the low-solid-content conductive welding type silver paste is sintered, and the TBC battery is prepared. By utilizing the method, the effects of the two silver pastes are mutually compensated, so that the photoelectric conversion efficiency of the prepared TBC battery is kept unchanged, the total consumption of silver on the TBC battery is reduced, and the overall cost of the prepared TBC battery is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present invention relate to the technical field of solar cells, and in particular to a printing preparation method of a TBC cell and a TBC cell. Background Art

[0002] The update and iteration of photovoltaic cell structure has led to the continuous accumulation of old production capacity, and cost reduction and efficiency improvement have become the key issues of the photovoltaic industry. Compared with P-type crystalline silicon cells, N-type crystalline silicon cells have a longer minority carrier life, no photoinduced degradation, good weak light effect, and a small temperature coefficient, which is the hope for crystalline silicon solar cells to break through the theoretical maximum efficiency.

[0003] Among them, the TBC cell is a crystalline silicon solar cell with a back contact structure. It is a structure of TOPCon (Tunnel Oxide Passivated Contact) superimposed on BC (Back Contact) technology. On the back of the cell, there are P and N regions with good quality and arranged in a forked finger shape. The characteristics of the TBC cell are that the PN junction and metal contact are both on the back of the cell, and the front side (i.e., the light-receiving side) is not affected by any metal grid line blocking, so it has a higher short-circuit current. At the same time, the back side can allow wider metal grid lines to reduce the series resistance and thus improve the fill factor. In addition, the open-circuit voltage gain brought by the front surface field of the cell and the good passivation effect makes the photoelectric conversion efficiency of this cell with no obstruction on the front side high.

[0004] Silver paste is a conductive paste containing silver particles. When used in the preparation of TBC batteries, it can improve the conductivity and photoelectric conversion efficiency of TBC batteries. At present, the silver paste consumption corresponding to TBC batteries is 85 mg / piece, and the price of silver paste is roughly 7,000 yuan / kg, and the silver paste cost corresponding to TBC batteries accounts for more than 60% of non-silicon costs. With the reduction of the unit price of TBC batteries, improving efficiency and reducing costs are urgent issues that the solar cell industry needs to solve, and reducing the silver paste consumption corresponding to TBC batteries is the most effective method besides the cost of silicon wafers. Summary of the invention

[0005] The embodiment of the present invention provides a printing preparation method of a TBC battery and a TBC battery, which effectively reduces the consumption of silver, realizes cost optimization of the TBC battery, achieves the effect of reducing costs and increasing efficiency, and improves the overall cost performance of the TBC battery.

[0006] In a first aspect, an embodiment of the present invention provides a printing preparation method of a TBC battery, comprising:

[0007] Preparation of corrosion contact type silver paste, and preparation of low solid content conductive welding type silver paste;

[0008] Printing the corrosion contact type silver paste on the first surface of the TBC battery semi-finished product to form a grid line, and drying the TBC battery semi-finished product printed with the corrosion contact type silver paste; wherein the first surface of the TBC battery semi-finished product includes a first area and a second area alternately arranged in an interdigitated shape, and the grid lines are formed in the first area and the second area respectively;

[0009] The low-solid conductive soldering silver paste is overprinted on the grid line, and the TBC battery semi-finished product overprinted with the low-solid conductive soldering silver paste is sintered to obtain the TBC battery.

[0010] Optionally, the raw materials of the corrosion contact type silver paste include a first organic additive, a first micron-sized spherical silver powder, a nano-sized spherical silver powder, a first organic binder and a first glass powder;

[0011] Prepare a corrosion contact type silver paste, including:

[0012] Mixing and dispersing the nanoscale spherical silver powder, the first glass powder and the first organic binder to obtain a uniformly mixed first powder;

[0013] adding the first micron-sized spherical silver powder to the first powder, and dispersing and grinding the first powder and the first micron-sized spherical silver powder to obtain a uniformly mixed second powder;

[0014] The first organic additive is added to the second powder, and the second powder and the first organic additive are dispersed to obtain the uniformly mixed corrosion contact type silver paste.

[0015] Optionally, the mass percentage of the first organic additive in the corrosion contact type silver paste is between 0.5% and 1%; the mass percentage of the first micron-sized spherical silver powder in the corrosion contact type silver paste is between 72% and 78%; the mass percentage of the nano-sized spherical silver powder in the corrosion contact type silver paste is between 4% and 6%; the mass percentage of the first organic binder in the corrosion contact type silver paste is between 10% and 20.5%; the mass percentage of the first glass powder in the corrosion contact type silver paste is between 3% and 5%.

[0016] Optionally, the first organic additive comprises hydrogenated castor oil.

[0017] Optionally, the first organic binder includes a first high molecular polymer and a first organic solvent;

[0018] The mass percentage of the first high molecular polymer in the first organic binder is between 8% and 10%; the mass percentage of the first organic solvent in the first organic binder is between 90% and 92%.

[0019] Optionally, the first glass powder includes Bi 2 O 3 , AL 2 O 3 、SiO 2 , ZnO, Sb 2 O 5 , B 2 O 3 and TeO 3 ; wherein, the Bi 2 O 3 The mass percentage of the first glass powder is between 15% and 22%; 2 O 3 The mass percentage of the first glass powder is between 8% and 18%; 2 The mass percentage of the first glass powder is between 12% and 20%; the mass percentage of the ZnO in the first glass powder is between 15% and 25%; 2 O 5 The mass percentage of the first glass powder is between 18% and 25%; 2 O 3 The mass percentage of the first glass powder is between 10% and 15%; the TeO 3 The mass percentage of the first glass powder is between 20% and 30%.

[0020] Optionally, the raw materials of the low-solid conductive soldering type silver paste include a second organic additive, a second micron-sized spherical silver powder, a second organic binder and a second glass powder;

[0021] Preparation of low solid conductive soldering silver paste, including:

[0022] Mixing and dispersing the second micron-sized spherical silver powder, the second glass powder and the second organic binder to obtain a uniformly mixed third powder;

[0023] The second organic additive is added to the third powder, and the third powder and the second organic additive are dispersed to obtain the low-solid conductive soldering type silver paste that is evenly mixed.

[0024] Optionally, the mass percentage of the second organic additive in the low-solid conductive soldering type silver paste is between 0.5% and 1.2%; the mass percentage of the second micron-sized spherical silver powder in the low-solid conductive soldering type silver paste is between 43% and 48%; the mass percentage of the second organic binder in the low-solid conductive soldering type silver paste is between 47.8% and 54%; the mass percentage of the second glass powder in the low-solid conductive soldering type silver paste is between 2.5% and 3%.

[0025] Optionally, the second organic additive comprises polyvinyl alcohol.

[0026] Optionally, the second organic binder includes a second high molecular polymer and a second organic solvent;

[0027] The mass percentage of the second high molecular polymer in the second organic binder is between 22% and 25%; the mass percentage of the second organic solvent in the second organic binder is between 75% and 78%.

[0028] Optionally, the second glass powder includes Bi 2 O 3 , AL 2 O 3 、SiO 2 , ZnO, Sb 2 O 5 , B 2 O 3 and TeO 3 ; wherein, the Bi 2 O 3 The mass percentage of the second glass powder is between 12% and 32%; 2 O 3 The mass percentage of the second glass powder is between 6% and 15%; 2 The mass percentage of the second glass powder is between 10% and 20%; the mass percentage of the ZnO in the second glass powder is between 10% and 22%; 2 O 5 The mass percentage of the second glass powder is between 10% and 22%; 2 O 3 The mass percentage of the second glass powder is between 10% and 15%; the TeO 3 The mass percentage of the second glass powder is between 10% and 25%.

[0029] In a second aspect, an embodiment of the present invention further provides a TBC battery, which is prepared using the printing preparation method of the TBC battery as described in any one of the first aspects.

[0030] An embodiment of the present invention provides a printing preparation method for a TBC battery and a TBC battery. The printing preparation method first prepares a corrosion contact type silver paste and a low-solid conductive welding type silver paste, then prints the corrosion contact type silver paste on the first surface of a TBC battery semi-finished product to form a grid line, and dries the TBC battery semi-finished product printed with the corrosion contact type silver paste; wherein the first surface of the TBC battery semi-finished product includes a first region and a second region alternately arranged in a forked shape, and the grid lines are formed in the first region and the second region, respectively; finally, a low-solid conductive welding type silver paste is overprinted on the grid line, and the TBC battery semi-finished product overprinted with the low-solid conductive welding type silver paste is sintered to obtain the TBC battery. The method provides a novel and efficient grid-stack overprinting silver paste production process for TBC cells. The corrosion contact type silver paste and the low-solid conductive welding type silver paste are sequentially printed. The corrosion contact type silver paste is first printed on the TBC cell semi-finished product. The corrosion contact type silver paste can corrode the silicon nitride and the doping layer on the surface of the TBC cell semi-finished product, so that the corrosion contact type silver paste and the surface of the TBC cell semi-finished product form good contact, better collect electrons, and facilitate the grid line to be stably retained on the surface of the TBC cell semi-finished product. The low-solid conductive welding type silver paste is then overprinted on the grid line, so that the TBC cell has a good electron collection function and can be used as a welding material in the subsequent solar module section. The effects of the two silver pastes compensate each other, so that the photoelectric conversion efficiency of the TBC cell finally prepared remains unchanged. The silver content of low-solid conductive welding silver paste is lower, which reduces the total silver consumption of the two silver pastes on the TBC battery. The overall weight of the TBC battery finally prepared is reduced accordingly, and the overall cost is reduced, thus realizing the cost optimization of the TBC battery, which can achieve the effect of reducing costs and increasing efficiency, improve the overall cost performance of the TBC battery finally prepared, and enhance the competitiveness of the TBC battery in the industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0032] Figure 1 It is a schematic diagram of a process of printing and preparing a TBC battery provided by an embodiment of the present invention;

[0033] Figure 2 It is a schematic diagram of a process of another printing preparation method of a TBC battery provided by an embodiment of the present invention;

[0034] Figure 3It is a schematic flow chart of another printing preparation method of a TBC battery provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0035] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. It is to be understood that the specific embodiments described herein are only used to explain the present invention, rather than to limit the present invention. It should also be noted that, for ease of description, only parts related to the present invention, rather than all structures, are shown in the accompanying drawings.

[0036] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. It should be noted that the directional words such as "upper", "lower", "left", "right" and the like described in the embodiments of the present invention are described at the angles shown in the accompanying drawings and should not be understood as limitations on the embodiments of the present invention. In addition, in the context, it is also necessary to understand that when it is mentioned that an element is formed "on" or "under" another element, it can not only be directly formed "on" or "under" another element, but also indirectly formed "on" or "under" another element through an intermediate element. The terms "first", "second", etc. are only used for descriptive purposes and do not represent any order, quantity or importance, but are only used to distinguish different components. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood in specific circumstances.

[0037] The term “including” and its variations used in the present invention are open inclusions, that is, “including but not limited to.” The term “based on” means “based at least in part on.” The term “one embodiment” means “at least one embodiment.”

[0038] It should be noted that the concepts such as "first" and "second" mentioned in the present invention are only used to distinguish the corresponding contents, and are not used to limit the order or interdependence.

[0039] It should be noted that the modifications of "one" and "plurality" mentioned in the present invention are illustrative rather than restrictive, and those skilled in the art should understand that, unless otherwise clearly indicated in the context, it should be understood as "one or more".

[0040] Figure 1 It is a schematic flow chart of a printing preparation method for a TBC battery provided in an embodiment of the present invention. The printing preparation method for the TBC battery can be applied to the process of forming an electrode structure by screen printing at the end of the preparation process of a semi-finished product of a TBC battery. The printing preparation method for the TBC battery can be used to prepare a TBC battery.

[0041] like Figure 1 As shown, the printing preparation method includes:

[0042] S110, preparing corrosion contact type silver paste, and preparing low solid content conductive welding type silver paste.

[0043] First of all, it should be noted that screen printing is one of the core processes in the manufacturing process of solar cells, and is mainly used for electrode formation of solar cells. This process uses the basic principle that the mesh holes of the graphic part of the screen are permeable to the slurry, and the mesh holes of the non-graphic part are not permeable to the slurry for printing. During the printing process, the slurry is accurately squeezed onto the TBC battery semi-finished product through the mesh holes of the screen, and the slurry is evenly distributed on the surface of the TBC battery in the form of a wire to form the required electrode pattern. Generally, the slurry for screen printing may include but is not limited to silver paste. The pattern formed by screen printing includes metal grid lines. High-temperature sintering is used to treat the electrode material screen-printed on the surface of the TBC battery at high temperature, dry the slurry on the surface of the TBC battery, burn out the organic components of the slurry, and the slurry can corrode through the passivation film layer and connect to the PN junction, so that the metal grid line forms a good ohmic contact with the substrate of the TBC battery, so as to achieve the purpose of collecting and conducting current.

[0044] Also, it should be noted that in the preparation process of TBC batteries, the silver content of the existing screen-printed silver paste is relatively high, which is not conducive to achieving the goal of reducing costs and increasing efficiency. Therefore, in this embodiment, corrosion contact type silver paste and low solid conductive welding type silver paste are additionally prepared, wherein the silver content of the corrosion contact type silver paste can be understood as the silver content of the existing silver paste, and the silver content of the low solid conductive welding type silver paste is lower than the silver content of the corrosion contact type silver paste. In this way, the subsequent use of corrosion contact type silver paste and low solid conductive welding type silver paste for screen printing can effectively reduce the total silver consumption of the two silver pastes on the TBC battery, thereby reducing the overall cost of the TBC battery and achieving the effect of reducing costs and increasing efficiency.

[0045] It is understandable that the corrosion contact type silver paste includes a variety of different raw materials, and the low solid conductive welding type silver paste also includes a variety of different raw materials. By setting the ratio of each component in these raw materials, the corrosion contact type silver paste and the low solid conductive welding type silver paste can be obtained respectively. The difference in the component ratio of the corrosion contact type silver paste and the low solid conductive welding type silver paste is mainly set to distinguish the functions of the two silver pastes. Among them, the main function of the corrosion contact type silver paste is to corrode the surface of the TBC battery semi-finished product to form a stable grid line, and the main function of the low solid conductive welding type silver paste is the subsequent welding of the solar module segment, which makes the components and mass percentages of the corrosion contact type silver paste and the low solid conductive welding type silver paste form the above-mentioned differences. Of course, when the specific needs are different, the component ratio of the corrosion contact type silver paste and the low solid conductive welding type silver paste can be adjusted according to actual needs.

[0046] S120, printing a corrosion contact type silver paste on the first surface of the TBC battery semi-finished product to form a gate line, and drying the TBC battery semi-finished product printed with the corrosion contact type silver paste; wherein the first surface of the TBC battery semi-finished product includes a first area and a second area alternately arranged in a forked shape, and the gate lines are formed in the first area and the second area, respectively.

[0047] Specifically, the TBC battery semi-finished product can be understood as a single crystal TBC silicon wafer, and its specifications can be 182.2mm×183.75mm. Exemplarily, a grid line can be formed on the first surface of the TBC battery semi-finished product by 520 mesh screen printing, and its wet weight is 17.2mg. In other words, the corrosion contact type silver paste is printed on the first surface of the TBC battery semi-finished product, and the grid line on the first surface of the TBC battery semi-finished product is a silver fine grid. After printing the corrosion contact type silver paste on the first surface of the TBC battery semi-finished product, the TBC battery semi-finished product printed with the corrosion contact type silver paste needs to be placed in a drying furnace for drying, and the drying temperature can be around 300 degrees Celsius.

[0048] S130, overprinting a low-solid conductive soldering silver paste on the grid line, and sintering the TBC battery semi-finished product overprinted with the low-solid conductive soldering silver paste to obtain a TBC battery.

[0049] Specifically, take a TBC battery semi-finished product printed with corrosion contact type silver paste and dried, and start printing low-solid conductive welding type silver paste. Exemplarily, it can be done by 520 mesh screen printing, and through precise positioning, the low-solid conductive welding type silver paste is required to be overprinted on the grid line of the corrosion contact type silver paste, and its wet weight is 21.1 mg. By overprinting, the precise pattern can be printed at the same grid line position to ensure that there will be no offset or repeated printing, thereby improving the performance and stability of the TBC battery. After overprinting the low-solid conductive welding type silver paste on the first surface of the TBC battery semi-finished product, the TBC battery semi-finished product printed with the low-solid conductive welding type silver paste needs to be placed in a drying furnace for sintering treatment, and the sintering temperature can be around 785 degrees Celsius. In this way, the desired TBC battery can be prepared.

[0050] In addition, it should be noted that the electrical data of the TBC battery prepared in this embodiment is tested to determine whether the electrical performance of the TBC battery meets the requirements, and to determine whether the total consumption of silver in the silver paste of the TBC battery and the overall cost are reduced. The electrical test data include: open circuit voltage of 0.7406V, short circuit current of 14.015A, fill factor of 85.45%, photoelectric conversion efficiency of 26.631%, and the total single-sided wet weight of the TBC battery is 38.3mg. In addition, the silver content of the low-solid conductive welding type silver paste only accounts for 45% of the total silver paste, which reduces the overall cost by more than 30%, and the photoelectric conversion efficiency remains unchanged. The test data meets the required requirements, indicating that the printing preparation method of this application can guarantee the performance requirements of the TBC battery. In this way, the printing preparation method provided in this embodiment can reduce the wet weight of printing, reduce costs and increase efficiency. The silver content of the low-solid conductive welding type silver paste is low, so that the total silver consumption of the two silver pastes on the TBC battery semi-finished product can be reduced. For example, the total silver consumption is reduced from the existing 85 mg / piece to 72 mg / piece, and the overall weight of the printed TBC battery is also reduced, effectively reducing the cost by 30%, thereby improving the overall cost performance and competitiveness of the printed TBC battery.

[0051] The technical solution in the embodiment of the present invention provides a new and efficient grid-stack overprinting silver paste production process for TBC batteries, which uses a corrosion contact type silver paste and a low-solid conductive welding type silver paste to be printed in sequence. The corrosion contact type silver paste is first printed on the TBC battery semi-finished product, and the corrosion contact type silver paste can corrode the silicon nitride and doping layer on the surface of the TBC battery semi-finished product, so that the corrosion contact type silver paste and the surface of the TBC battery semi-finished product form good contact, better collect electrons, and facilitate the grid line to be stably retained on the surface of the TBC battery semi-finished product; then the low-solid conductive welding type silver paste is overprinted on the grid line, so that the TBC battery has a good electron collection function and can be used as a welding material in the subsequent solar module section; the effects of the two silver pastes compensate each other, so that the photoelectric conversion efficiency of the TBC battery finally prepared remains unchanged. The silver content of low-solid conductive welding silver paste is lower, which reduces the total silver consumption of the two silver pastes on the TBC battery. The overall weight of the TBC battery finally prepared is reduced accordingly, and the overall cost is reduced, thus realizing the cost optimization of the TBC battery, which can achieve the effect of reducing costs and increasing efficiency, improve the overall cost performance of the TBC battery finally prepared, and enhance the competitiveness of the TBC battery in the industry.

[0052] Figure 2is a flow chart of another printing preparation method of a TBC battery provided by an embodiment of the present invention, and this embodiment is optimized on the basis of the above embodiment. Optionally, the raw materials of the corrosion contact type silver paste include a first organic additive, a first micron-sized spherical silver powder, a nano-sized spherical silver powder, a first organic binder and a first glass powder;

[0053] Prepare a corrosion contact type silver paste, including:

[0054] Mixing and dispersing the nano-scale spherical silver powder, the first glass powder and the first organic binder to obtain a uniformly mixed first powder;

[0055] Adding a first micron-sized spherical silver powder to the first powder, and dispersing and grinding the first powder and the first micron-sized spherical silver powder to obtain a uniformly mixed second powder;

[0056] The first organic additive is added to the second powder, and the second powder and the first organic additive are dispersed to obtain a uniformly mixed corrosion contact type silver paste.

[0057] For details not yet provided in this embodiment, please refer to the above embodiments. Figure 2 As shown, the printing preparation method includes:

[0058] S210, mixing and dispersing the nano-scale spherical silver powder, the first glass powder and the first organic binder to obtain a uniformly mixed first powder material.

[0059] Among them, the particle size of the nano-scale spherical silver powder is different from the particle size of the first micron-scale spherical silver powder. The nano-scale spherical silver powder is set because there is space between the first micron-scale spherical silver powder. The nano-scale spherical silver powder can be filled in the space of the first micron-scale spherical silver powder, which can play a role in reducing the resistivity of the grid line. The higher the purity of the nano-scale spherical silver powder, the better the conductivity of the prepared corrosion contact type silver paste, and then the better the conductivity of the TBC battery, which can effectively improve the utilization rate of the TBC battery power and extend the service life of the TBC battery. Exemplarily, the purity of the nano-scale spherical silver powder can be 99.9% or more. And, the first glass powder is an inorganic adhesive that can achieve the bonding of the nano-scale spherical silver powder and the first micron-scale spherical silver powder. The mass percentage of the first glass powder in the corrosion contact type silver paste can be adjusted later according to the total amount of the nano-scale spherical silver powder and the first micron-scale spherical silver powder. The particle size of the first glass powder directly affects the fluidity of the corrosion contact type silver paste. Generally, the first glass powder with a smaller particle size is easier to disperse in the corrosion contact type silver paste, thereby improving the fluidity and coating properties of the corrosion contact type silver paste. Exemplarily, the particle size range of the first glass powder can be 2μm to 2.5μm. In addition, the first organic adhesive is mainly used to disperse and print nano-scale spherical silver powder, and to bond the components before the first glass powder is started. The mass percentage of the first organic adhesive in the corrosion contact type silver paste can be adjusted later according to the total amount of nano-scale spherical silver powder and the first micron-scale spherical silver powder.

[0060] Specifically, after the nano-scale spherical silver powder, the first glass powder and the first organic binder are mixed, a disperser can be used to mix and stir them, which can provide a better dispersion effect, avoid aggregation or precipitation of the mixed first powder, and make the first powder more uniform after mixing.

[0061] S220, adding the first micron-sized spherical silver powder to the first powder, and dispersing and grinding the first powder and the first micron-sized spherical silver powder to obtain a uniformly mixed second powder.

[0062] Among them, the first micron-sized spherical silver powder is the conductive body of the corrosion contact type silver paste. The mass percentage of the first micron-sized spherical silver powder in the corrosion contact type silver paste can be adjusted later according to the conductivity requirements. The particle size of the first micron-sized spherical silver powder directly affects the conductive properties of the corrosion contact type silver paste. Generally, the smaller the particles of the first micron-sized spherical silver powder, the larger its surface area, thus providing more contact points, reducing resistance, thereby improving the conductive efficiency, that is, the better the conductive properties. Exemplarily, the particle diameter range of the first micron-sized spherical silver powder can be 1μm to 5μm. And, the higher the purity of the first micron-sized spherical silver powder, the better the conductive properties of the prepared corrosion contact type silver paste, and then the better the conductive properties of the TBC battery, which can effectively improve the utilization rate of the TBC battery power and extend the service life of the TBC battery. Exemplarily, the purity of the first micron-sized spherical silver powder can be 99.9% or more.

[0063] Specifically, the first micron-sized spherical silver powder is added to the first powder, and the first powder and the first micron-sized spherical silver powder are mixed and stirred by a disperser, and then the surface roughness of the mixed powder is reduced by a grinding device to obtain a relatively fine secondary powder.

[0064] S230, adding the first organic additive to the second powder, and dispersing the second powder and the first organic additive to obtain a uniformly mixed corrosion contact type silver paste, and preparing a low-solid conductive welding type silver paste.

[0065] Among them, the first organic additive has the characteristics of good weather resistance, corrosion resistance and strong activity, and can play a role in dispersion and dilution. The first organic additive can improve and adjust the performance of the formed corrosion contact type silver paste, maintain good printing shaping, and after the corrosion contact type silver paste is printed on the first surface of the TBC battery semi-finished product, it is beneficial to improve the overall performance of the TBC battery. The type of the first organic additive can be appropriately selected as needed, and optionally, the first organic additive includes hydrogenated castor oil.

[0066] Specifically, the first organic additive is added to the second powder, and the second powder and the first organic additive are continuously dispersed and mixed at high speed using a disperser to obtain the corrosion contact type silver paste of the present application.

[0067] The raw materials of the corrosion contact type silver paste include a first organic additive, a first micron-sized spherical silver powder, a nano-sized spherical silver powder, a first organic binder and a first glass powder. Optionally, the mass percentage of the first organic additive in the corrosion contact type silver paste is between 0.5% and 1%; the mass percentage of the first micron-sized spherical silver powder in the corrosion contact type silver paste is between 72% and 78%; the mass percentage of the nano-sized spherical silver powder in the corrosion contact type silver paste is between 4% and 6%; the mass percentage of the first organic binder in the corrosion contact type silver paste is between 10% and 20.5%; and the mass percentage of the first glass powder in the corrosion contact type silver paste is between 3% and 5%.

[0068] Specifically, each raw material component has a certain role in the corrosion contact type silver paste, and the above raw material components are formulated according to their mass percentage in the corrosion contact type silver paste, so that it is convenient to increase or decrease the solid content of each raw material component during formulation. In a specific embodiment, the mass percentage of the first organic additive in the corrosion contact type silver paste is 0.8%, the mass percentage of the first micron-sized spherical silver powder in the corrosion contact type silver paste is 75%, the mass percentage of the nano-sized spherical silver powder in the corrosion contact type silver paste is 4%, the mass percentage of the first organic binder in the corrosion contact type silver paste is 17.2%, and the mass percentage of the first glass powder in the corrosion contact type silver paste is 3%.

[0069] Optionally, the first organic adhesive comprises a first high molecular polymer and a first organic solvent; wherein the mass percentage of the first high molecular polymer in the first organic adhesive is between 8% and 10%; and the mass percentage of the first organic solvent in the first organic adhesive is between 90% and 92%.

[0070] Specifically, the first high molecular polymer mainly realizes a firm connection between two or more objects through the interaction between its molecular chain and the surface of the adherend, thereby improving the adhesion and bonding effect of the first organic adhesive. The first organic solvent can adjust the viscosity of the first organic adhesive so that it can achieve the best use effect, and can also make the first organic adhesive quickly solidify and improve production efficiency. Exemplarily, the first organic adhesive can include a first high molecular polymer with a mass percentage of 9% and a first organic solvent with a mass percentage of 91%. Exemplarily, the first high molecular polymer can include ethyl cellulose N50. Exemplarily, the first high molecular polymer can be a polymer with a low sintering residual viscoelastic modulus. Exemplarily, the first organic solvent can include five or more of pine oil, butyl carbitol, butyl carbitol acetate, tributyl citrate, Span 85 and alcohol ester twelve. In a specific embodiment, the first organic solvent can be composed of five components: pineol, butyl carbitol, butyl carbitol acetate, tributyl citrate, and Span 85, wherein the mass percentage of pineol in the first organic solvent is 10%, the mass percentage of butyl carbitol in the first organic solvent is 20%, the mass percentage of butyl carbitol acetate in the first organic solvent is 15%, the mass percentage of tributyl citrate in the first organic solvent is 15%, and the mass percentage of Span 85 in the first organic solvent is 40%. Each component in the first organic solvent has good solubility and stability. After being proportioned into the first organic solvent, the stability of the corrosion contact type silver paste can be effectively improved, so that the prepared corrosion contact type silver paste can be used for a long time.

[0071] Optionally, the first glass powder includes Bi 2 O 3 (bismuth trioxide), AL 2 O 3 (aluminum oxide), SiO 2 (Silicon dioxide), ZnO (zinc oxide), Sb 2 O 5 (antimony pentoxide), B 2 O 3 (boron trioxide) and TeO 3 (tellurium trioxide); among which, Bi 2 O 3 The mass percentage of AL in the first glass powder is between 15% and 22%; 2 O 3 The mass percentage of SiO in the first glass powder is between 8% and 18%; 2 The mass percentage of Sb in the first glass powder is between 12% and 20%; the mass percentage of ZnO in the first glass powder is between 15% and 25%; 2 O 5The mass percentage of B in the first glass powder is between 18% and 25%; 2 O 3 The mass percentage of TeO in the first glass powder is between 10% and 15%; 3 The mass percentage of the first glass powder is between 20% and 30%.

[0072] Specifically, the first glass powder may be made of Bi 2 O 3 , AL 2 O 3 、SiO 2 , ZnO, Sb 2 O 5 , B 2 O 3 and TeO 3 These components are mixed together in a certain proportion, melted at high temperature, and sintered and crushed to obtain. 2 O 3 The mass percentage of AL in the first glass powder is 15%, 2 O 3 The mass percentage of SiO in the first glass powder is 9%. 2 The mass percentage of the first glass powder is 12%, the mass percentage of ZnO in the first glass powder is 15%, and the mass percentage of Sb 2 O 5 The mass percentage of B in the first glass powder is 19%, 2 O 3 The mass percentage of TeO in the first glass powder is 10%. 3 The mass percentage in the first glass frit is 20%.

[0073] S240, printing a corrosion contact type silver paste on the first surface of the TBC battery semi-finished product to form a gate line, and drying the TBC battery semi-finished product printed with the corrosion contact type silver paste; wherein the first surface of the TBC battery semi-finished product includes a first area and a second area alternately arranged in a forked shape, and the gate lines are formed in the first area and the second area, respectively.

[0074] S250, overprinting a low-solid conductive soldering silver paste on the grid line, and sintering the TBC battery semi-finished product overprinted with the low-solid conductive soldering silver paste to obtain a TBC battery.

[0075] Figure 3 is a schematic flow chart of another printing preparation method of a TBC battery provided by an embodiment of the present invention, and this embodiment is optimized on the basis of the above embodiment. Optionally, the raw materials of the low-solid conductive soldering type silver paste include a second organic additive, a second micron-sized spherical silver powder, a second organic binder and a second glass powder;

[0076] Preparation of low solid conductive soldering silver paste, including:

[0077] The second micron-sized spherical silver powder, the second glass powder and the second organic binder are mixed and dispersed to obtain a uniformly mixed third powder;

[0078] The second organic additive is added to the third powder, and the third powder and the second organic additive are dispersed to obtain a uniformly mixed low-solid conductive soldering silver paste.

[0079] For details not yet provided in this embodiment, please refer to the above embodiments. Figure 3 As shown, the printing preparation method includes:

[0080] S310, mixing and dispersing the second micron-sized spherical silver powder, the second glass powder and the second organic binder to obtain a uniformly mixed third powder material.

[0081] Among them, the second micron-sized spherical silver powder is the conductive main body of the low-solid conductive welding type silver paste. The mass percentage of the second micron-sized spherical silver powder in the low-solid conductive welding type silver paste can be adjusted later according to the conductive requirements. The particle size of the second micron-sized spherical silver powder directly affects the conductive properties of the low-solid conductive welding type silver paste. Generally, the smaller the particles of the second micron-sized spherical silver powder, the larger its surface area, thus providing more contact points, reducing resistance, thereby improving the conductive efficiency, that is, the better the conductive properties. Exemplarily, the particle diameter range of the second micron-sized spherical silver powder can be 2μm to 6μm. And, the higher the purity of the second micron-sized spherical silver powder, the better the conductive properties of the prepared low-solid conductive welding type silver paste, and then the better the conductive properties of the TBC battery, which can effectively improve the utilization rate of the TBC battery power and extend the service life of the TBC battery. Exemplarily, the purity of the second micron-sized spherical silver powder can be 99.9% or more. And, the second glass powder is an inorganic adhesive that can achieve mutual bonding of the second micron-sized spherical silver powder. The mass percentage of the second glass powder in the low-solid conductive welding type silver paste can be adjusted according to the total amount of the second micron-sized spherical silver powder. The particle size of the second glass powder directly affects the fluidity of the low-solid conductive welding type silver paste. Generally, the second glass powder with a smaller particle size is easier to disperse in the low-solid conductive welding type silver paste, thereby improving the fluidity and coating properties of the low-solid conductive welding type silver paste. Exemplarily, the particle size range of the second glass powder can be 1.5μm to 2.2μm. And, the second organic adhesive is mainly used to disperse and print the second micron-sized spherical silver powder, and to bond the components before the second glass powder is started. The mass percentage of the second organic adhesive in the low-solid conductive welding type silver paste can be adjusted according to the total amount of the second micron-sized spherical silver powder.

[0082] Specifically, after the second micron-sized spherical silver powder, the second glass powder and the second organic binder are mixed, a disperser can be used to mix and stir them, which can provide a better dispersion effect, avoid aggregation or precipitation of the mixed third powder, and make the third powder more uniform after mixing.

[0083] S320, adding the second organic additive to the third powder, and dispersing the third powder and the second organic additive to obtain a uniformly mixed low-solid conductive soldering silver paste, and preparing a corrosion contact silver paste.

[0084] Among them, the second organic additive has good lubrication and plasticization characteristics. The second organic additive can improve and adjust the performance of the formed low-solid conductive welding type silver paste, increase the conductivity of the low-solid conductive welding type silver paste, improve the fluidity and viscosity of the low-solid conductive welding type silver paste, make it easier to coat and shape, and after the low-solid conductive welding type silver paste is printed on the first surface of the TBC battery semi-finished product, it is beneficial to improve the overall performance of the TBC battery. The type of the second organic additive can be appropriately selected as needed. Optionally, the second organic additive includes polyvinyl alcohol.

[0085] Specifically, the second organic additive is added to the third powder, and the third powder and the second organic additive are continuously dispersed and mixed at high speed using a disperser to obtain the low-solid conductive soldering silver paste of the present application.

[0086] The raw materials of the low-solid conductive soldering type silver paste include a second organic additive, a second micron-sized spherical silver powder, a second organic binder, and a second glass powder. Optionally, the mass percentage of the second organic additive in the low-solid conductive soldering type silver paste is between 0.5% and 1.2%; the mass percentage of the second micron-sized spherical silver powder in the low-solid conductive soldering type silver paste is between 43% and 48%; the mass percentage of the second organic binder in the low-solid conductive soldering type silver paste is between 47.8% and 54%; the mass percentage of the second glass powder in the low-solid conductive soldering type silver paste is between 2.5% and 3%.

[0087] Specifically, unlike the printed corrosion contact type silver paste, the component ratio of the low solid conductive welding type silver paste is different from that of the corrosion contact type silver paste; and the role of each raw material component of the low solid conductive welding type silver paste can refer to the role of each raw material component in the corrosion contact type silver paste, which will not be repeated here.

[0088] It should be emphasized that the second micron-sized spherical silver powder, as the conductive main body of the low-solid conductive soldering silver paste, has a mass percentage of 43% to 48%. Compared with the first micron-sized spherical silver powder of 72% to 78% in the corrosion contact silver paste, the content of silver powder in the low-solid conductive soldering silver paste is much lower. In this way, the total content of silver powder in the corrosion contact silver paste and the low-solid conductive soldering silver paste is greatly reduced, which plays a role in reducing costs. In a specific embodiment, the mass percentage of the second organic additive in the low-solid conductive soldering silver paste is 0.8%; the mass percentage of the second micron-sized spherical silver powder in the low-solid conductive soldering silver paste is 45%; the mass percentage of the second organic binder in the low-solid conductive soldering silver paste is 51.7%; the mass percentage of the second glass powder in the low-solid conductive soldering silver paste is 2.5%.

[0089] Optionally, the second organic binder includes a second high molecular polymer and a second organic solvent; wherein the mass percentage of the second high molecular polymer in the second organic binder is between 22% and 25%; and the mass percentage of the second organic solvent in the second organic binder is between 75% and 78%.

[0090] Specifically, the second high molecular polymer mainly realizes a firm connection between two or more objects through the interaction between its molecular chain and the surface of the adherend, thereby improving the adhesion and bonding effect of the second organic adhesive. The second organic solvent can adjust the viscosity of the second organic adhesive so that it can achieve the best use effect, and can also make the second organic adhesive quickly solidify and improve production efficiency. Exemplarily, the second organic adhesive can include a second high molecular polymer with a mass percentage of 23% and a second organic solvent with a mass percentage of 77%. Exemplarily, the second high molecular polymer can include N100. Exemplarily, the second high molecular polymer can be a polymer with a low sintering residual viscoelastic modulus. Exemplarily, the second organic solvent can include four or more of pine oil, butyl carbitol, butyl carbitol acetate, tributyl citrate, Span 85 and alcohol ester twelve. In a specific embodiment, the second organic solvent can be composed of four components: terpineol, butyl carbitol, butyl carbitol acetate, and tributyl citrate, wherein the mass percentage of terpineol in the second organic solvent is 20%, the mass percentage of butyl carbitol in the second organic solvent is 10%, the mass percentage of butyl carbitol acetate in the second organic solvent is 30%, and the mass percentage of tributyl citrate in the second organic solvent is 40%.

[0091] Optionally, the second glass powder includes Bi 2 O 3 (bismuth trioxide), AL 2 O 3 (aluminum oxide), SiO2 (Silicon dioxide), ZnO (zinc oxide), Sb 2 O 5 (antimony pentoxide), B 2 O 3 (boron trioxide) and TeO 3 (tellurium trioxide); among which, Bi 2 O 3 The mass percentage of AL in the second glass powder is between 12% and 32%; 2 O 3 The mass percentage of SiO in the second glass powder is between 6% and 15%; 2 The mass percentage of Sb in the second glass powder is between 10% and 20%; the mass percentage of ZnO in the second glass powder is between 10% and 22%; 2 O 5 The mass percentage of B in the second glass powder is between 10% and 22%; 2 O 3 The mass percentage of TeO in the second glass powder is between 10% and 15%; 3 The mass percentage of the second glass powder is between 10% and 25%.

[0092] Specifically, the second glass powder may be made of Bi 2 O 3 , AL 2 O 3 、SiO 2 , ZnO, Sb 2 O 5 , B 2 O 3 and TeO 3 These components are mixed together in a certain proportion, melted at high temperature, and sintered and crushed to obtain. 2 O 3 The mass percentage of AL in the second glass powder is 15%, 2 O 3 The mass percentage of SiO in the second glass powder is 12%. 2 The mass percentage of the second glass powder is 15%, the mass percentage of ZnO in the second glass powder is 12%, and the mass percentage of Sb 2 O 5 The mass percentage of B in the second glass powder is 15%, 2 O 3 The mass percentage of TeO in the second glass powder is 15%. 3 The mass percentage in the second glass frit is 16%.

[0093] S330, printing a corrosion contact type silver paste on the first surface of the TBC battery semi-finished product to form a gate line, and drying the TBC battery semi-finished product printed with the corrosion contact type silver paste; wherein the first surface of the TBC battery semi-finished product includes a first area and a second area alternately arranged in a forked shape, and the gate lines are formed in the first area and the second area, respectively.

[0094] S340, overprinting a low-solid conductive soldering silver paste on the grid line, and sintering the TBC battery semi-finished product overprinted with the low-solid conductive soldering silver paste to obtain a TBC battery.

[0095] Based on the same inventive concept, an embodiment of the present invention further provides a TBC battery. The TBC battery is prepared by a printing preparation method of a TBC battery provided in any one of the embodiments of the present invention. Therefore, the TBC battery has functional modules and beneficial effects corresponding to the printing preparation method of the TBC battery.

[0096] Note that the above are only preferred embodiments of the present invention and the technical principles used. Those skilled in the art will understand that the present invention is not limited to the specific embodiments described herein, and that various obvious changes, readjustments, combinations and substitutions can be made by those skilled in the art without departing from the scope of protection of the present invention. Therefore, although the present invention has been described in more detail through the above embodiments, the present invention is not limited to the above embodiments, and may include more other equivalent embodiments without departing from the concept of the present invention, and the scope of the present invention is determined by the scope of the appended claims.

Claims

1. A printing preparation method for a TBC battery, characterized in that: include: Preparation of corrosion contact type silver paste, and preparation of low solid content conductive welding type silver paste; Printing the corrosion contact type silver paste on the first surface of the TBC battery semi-finished product to form a grid line, and drying the TBC battery semi-finished product printed with the corrosion contact type silver paste; wherein the first surface of the TBC battery semi-finished product includes a first area and a second area alternately arranged in an interdigitated shape, and the grid lines are formed in the first area and the second area respectively; The low-solid conductive soldering silver paste is overprinted on the grid line, and the TBC battery semi-finished product overprinted with the low-solid conductive soldering silver paste is sintered to obtain the TBC battery.

2. The printing preparation method according to claim 1, characterized in that: The raw materials of the corrosion contact type silver paste include a first organic additive, a first micron-sized spherical silver powder, a nano-sized spherical silver powder, a first organic binder and a first glass powder; Prepare a corrosion contact type silver paste, including: Mixing and dispersing the nanoscale spherical silver powder, the first glass powder and the first organic binder to obtain a uniformly mixed first powder; adding the first micron-sized spherical silver powder to the first powder, and dispersing and grinding the first powder and the first micron-sized spherical silver powder to obtain a uniformly mixed second powder; The first organic additive is added to the second powder, and the second powder and the first organic additive are dispersed to obtain the uniformly mixed corrosion contact type silver paste.

3. The printing preparation method according to claim 2, characterized in that: The mass percentage of the first organic additive in the corrosion contact type silver paste is between 0.5% and 1%; the mass percentage of the first micron-sized spherical silver powder in the corrosion contact type silver paste is between 72% and 78%; the mass percentage of the nano-sized spherical silver powder in the corrosion contact type silver paste is between 4% and 6%; the mass percentage of the first organic binder in the corrosion contact type silver paste is between 10% and 20.5%; the mass percentage of the first glass powder in the corrosion contact type silver paste is between 3% and 5%.

4. The printing preparation method according to claim 2, characterized in that: The first organic additive includes hydrogenated castor oil.

5. The printing preparation method according to claim 2, characterized in that: The first organic binder includes a first high molecular polymer and a first organic solvent; The mass percentage of the first high molecular polymer in the first organic binder is between 8% and 10%; the mass percentage of the first organic solvent in the first organic binder is between 90% and 92%.

6. The printing preparation method according to claim 2, characterized in that: The first glass powder includes Bi2O3, AL2O3, SiO2, ZnO, Sb2O5, B2O3 and TeO3; wherein the mass percentage of Bi2O3 in the first glass powder is between 15% and 22%; the mass percentage of AL2O3 in the first glass powder is between 8% and 18%; the mass percentage of SiO2 in the first glass powder is between 12% and 20%; the mass percentage of ZnO in the first glass powder is between 15% and 25%; the mass percentage of Sb2O5 in the first glass powder is between 18% and 25%; the mass percentage of B2O3 in the first glass powder is between 10% and 15%; and the mass percentage of TeO3 in the first glass powder is between 20% and 30%.

7. The printing preparation method according to claim 1, characterized in that: The raw materials of the low-solid conductive soldering silver paste include a second organic additive, a second micron-sized spherical silver powder, a second organic binder and a second glass powder; Preparation of low solid conductive soldering silver paste, including: Mixing and dispersing the second micron-sized spherical silver powder, the second glass powder and the second organic binder to obtain a uniformly mixed third powder; The second organic additive is added to the third powder, and the third powder and the second organic additive are dispersed to obtain the low-solid conductive soldering type silver paste that is evenly mixed.

8. The printing preparation method according to claim 7, characterized in that: The mass percentage of the second organic additive in the low-solid conductive soldering type silver paste is between 0.5% and 1.2%; the mass percentage of the second micron-sized spherical silver powder in the low-solid conductive soldering type silver paste is between 43% and 48%; the mass percentage of the second organic binder in the low-solid conductive soldering type silver paste is between 47.8% and 54%; the mass percentage of the second glass powder in the low-solid conductive soldering type silver paste is between 2.5% and 3%.

9. The printing preparation method according to claim 7, characterized in that: The second organic additive includes polyvinyl alcohol.

10. The printing preparation method according to claim 7, characterized in that: The second organic binder includes a second high molecular polymer and a second organic solvent; The mass percentage of the second high molecular polymer in the second organic binder is between 22% and 25%; the mass percentage of the second organic solvent in the second organic binder is between 75% and 78%.

11. The printing preparation method according to claim 7, characterized in that: The second glass powder includes Bi2O3, AL2O3, SiO2, ZnO, Sb2O5, B2O3 and TeO3; wherein the mass percentage of Bi2O3 in the second glass powder is between 12% and 32%; the mass percentage of AL2O3 in the second glass powder is between 6% and 15%; the mass percentage of SiO2 in the second glass powder is between 10% and 20%; the mass percentage of ZnO in the second glass powder is between 10% and 22%; the mass percentage of Sb2O5 in the second glass powder is between 10% and 22%; the mass percentage of B2O3 in the second glass powder is between 10% and 15%; and the mass percentage of TeO3 in the second glass powder is between 10% and 25%.

12. A TBC battery, characterized in that: The TBC battery is prepared by the printing preparation method according to any one of claims 1 to 11.